CROWN LAND DISPOSAL IN THE CAPE OF GOOD HOPE 1853-1914 (Historia, 2021)
"The main asset of this Colony is its land".1 So stated an editorial in the Eastern Pro-mnce Herald in 1895, which might well have been written at any period during the nineteenth century, not only in the Cape of Good Hope but in many of the "New Lands" being colonized at the time.2 The disposal of land to settlers was a conscious act of government, often for specific purposes. Rarely were objectives clearly perceived or pursued, with the result that the key issue of access to land was liable to abrupt reformulations. 3 Conflicts of interest, speculation, and settlement disasters were the outcome of land policies in many countries throughout the last century, put the end result was the transfer of Crown and government land to private ownership on a scale without parallel before or since. The Cape Colony was no exception to these observations. In the period between the attainment of representative government in 1853 and the First World War, the Cape Colony disposed of some 26,3 million hectares under a series of enactments primarily designed to promote settlement and raise revenue (Table 1).4 The rate of alienation varied according to the recurrence of drought, economic cycles, and political crises (Fig 1). However, the options open to the Cape government were limited by the poor physical environment and lack of agricultural immigrants. Added to this was the inheritance of past modes of operation which acted as a break upon the progress of legislation and settlement.
Keywords: Uncontrolled frontier; Inheritance; History; Crown land disposal; indigenous population; Land policies; Cape-Dutch inheritance; Cape of Good Hope; British Imperial policies; Crown Lands Act of 1878; Legislative programmes